Healthy Living: DETERMINE Your Nutritional Health - Linda B. Bobroff (EDIS)
Revised! FCS8547, a 4-page fact sheet by Linda B.Bobroff, provides a checklist to determine whether an older person is at nutritional risk and additional information about warning signs of poor nutritional health. Published by the UF Department of Family Youth and Community Sciences, November 2010.